2018
DOI: 10.1111/wej.12394
|View full text |Cite
|
Sign up to set email alerts
|

Water footprint assessment considering intermediate products: model and a 2016 case study of China

Abstract: Analysing intermediate products within a water footprint (WF) across different economic sectors can show the root causes of water usage and is helpful for water resource management and policy making. However, conventional methods and data for a WF rarely assess the input and output of intermediate products directly and comprehensively. Therefore, this study proposes an approach to access the WF of intermediate products as well as final products in each sector of an economy’s water sustainability profile. An Ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Most countries do not have a large‐scale VWS implementation plan (Chouchane et al, 2018; Hoekstra, 2013; Qu et al, 2018; Zhao et al, 2015). Although a few countries (e.g., Jordan and Israel) have adopted a VWS, most countries are not importing or exporting VW following the theoretical direction of a VWS (Horlemann & Neubert, 2007; WWAP, 2016; Zhi et al, 2019). Water‐rich regions are not making full use of their water resources and exporting VW, whereas some water‐scarce regions overuse their local water resources in producing exported products, which exacerbates the water shortage (WWAP/UN‐Water, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Most countries do not have a large‐scale VWS implementation plan (Chouchane et al, 2018; Hoekstra, 2013; Qu et al, 2018; Zhao et al, 2015). Although a few countries (e.g., Jordan and Israel) have adopted a VWS, most countries are not importing or exporting VW following the theoretical direction of a VWS (Horlemann & Neubert, 2007; WWAP, 2016; Zhi et al, 2019). Water‐rich regions are not making full use of their water resources and exporting VW, whereas some water‐scarce regions overuse their local water resources in producing exported products, which exacerbates the water shortage (WWAP/UN‐Water, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Serrano et al [14] researched 27 EU states on their virtual water trade data and found out that Germany became a key net importer of water in Europe through the trade of agricultural products, foods, chemicals, and electricity. Zhi et al [15] described the intermediate water footprint products of each sector in a material-product network, and found out that the top three sectors with the largest water footprint in China were agriculture, food and machinery manufacturing in 2016. In line with the above literature, the amount of virtual water trade on the macro-industry level of one country (region) is usually calculated through an input-output model.…”
Section: Introductionmentioning
confidence: 99%